COMPOSITION AND AMOUNT OF MARINE DEBRIS IN THE MANGROVE AREA IN MENGKAPAN VILLAGE, SUNGAI APIT DISTRICT, SIAK REGENCY, RIAU PROVINCE - Silmarita, Silmarita; Fauzi, Muhammad; Sumiarsih, Eni (Asian Journal of Aquatic Sciences, 2019)
Marine debris is a type of pollutant that commonly found in the mangrove ecosystem. A study aims to investigate the composition, amount and oceanographic parameters that influence the presence of marine debris in Mengkapan mangrove ecotourism area has been conducted from June to August 2018. A survey method was used in this study. Sampling was done three times (once/ two weeks) in 3 observation stations. There were 3 stations namely S1 (settlement area), S2 (ecotourism area) and S3 (port area). Marine debris were collected from 3 plots (10 x 10 m) placed along the transect line. Results shown that the types of marine debris found in the observation area were plastic, glass, rubber, fabric, styrofoam, nets, cans, and paper. The most common debris found is plastic (2,603 items/m2). Total amount of marine debris in the Mengkapan area is 3,232 items/m2 (18.497 grams/m2). Macrodebris is the most common debris found